Comparative Analysis of the Performance of Four Symmetric Algorithms on Digital File Security - Manurung, Rodiyah Aini; Sutarman, Sutarman; Efendi, Syahril (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2025)
Information security is crucial to prevent misuse that could harm others. Information can be accessed through various electronic devices such as mobile phones, computers, and tablets in the form of text, images, audio, and video, whether public or confidential. In the digital era, image files are highly susceptible to authenticity risks as they can be easily shared through various communication media. This facilitates unrestricted digital file exchange, raising concerns about authenticity and the risk of modifications before reaching the recipient. Therefore, digital file exchanges require a security system to ensure that transmitted data remains original and intact. Cryptography is a field of study that protects data security in communication. It consists of algorithms and keys, where algorithms perform encryption and decryption, while keys enhance security levels. This study examines image encryption by using different key lengths with the same image, as well as encrypting images of varying sizes using the same key length, employing AES, DES, 3DES, and RC6 algorithms. The results show that the DES algorithm is the fastest in encryption and decryption compared to the other three algorithms. DES is 13.3% faster than 3DES and 10.2% faster than RC6. Additionally, the key length used does not significantly impact processing time, but image size greatly affects encryption and decryption speed. These findings indicate that in cryptographic implementations for digital images, file size is a critical factor to consider to maintain efficiency without compromising encryption and decryption speed